METODE PECS (PICTUE EXCHANGE COMMUNICATION SYSTEM) TERHADAP KEMAMPUAN KOMUNIKASI NON VERBAL ANAK - PRASETYO HERMAWAN, MARIO (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Communication was a dynamic process which used language as the main equipment at the moment an individual was doing social relationship with the other individuals which involved feeling expression, conveying idea, willing, needs, and purpose inside. Autism itself had obstacle such as behavior, communication, and social. In the communication there was non-verbal communication. Based on the problem, the autism children required PECS (Picture Exchange communication System) method. The method of PECS (Picture Exchange communication System) was an approach to train communication using verbal symbols. The purpose of this research was to know whether there was influence of PECS (Picture Exchange communication System) method toward non-verbal communication to autism children in YP PG/TK Puri Mutiara Bunda Sidoarjo or not. The method of this research used was quantitative pre experiment kind. The design used one group pre-test post-test with 6 subjects of autism children. The technique of data collection used was treatment test. The test was done to obtain the quantitative data about non-verbal ability using PECS (Picture Exchange communication System) method. The research result was proven that non-verbal communication ability using PECS (Picture Exchange communication System) method was obtained ZH value = 2,05. Because ZH value was 2,05 (above / greater than 1,96) so it could be concluded that Ho (Null hypothesis) was refused and Ha (Work hypothesis) was accepted. If Ha was accepted it meant there was influence of using PECS (Picture Exchange communication System) method toward non-verbal communication ability to autism children in YP PG/TK Puri Mutiara Bunda Sidoarjo.     Keywords: PECS (Picture Exchange communication System) method, non-verbal communication